The Urgency of Notary Position in the Establishment of Startups in Indonesia - KUSUMA, I Made Kristian Yuda; SUJANA, I Nyoman; SETIASA, Made (Journal of Political And Legal Sovereignty, 2025)
Purpose:This study aims to determine and analyze the normative authority of notaries in assisting the establishment of startups according to the Notary Law and to determine and analyze the role of notaries in guaranteeing the legality of documents and preventing internal conflicts.Methodology:The method used is a normative juridical approach with a study of laws and notarial practices. This research is classified as normative legal research. According to Peter Mahmud Marzuki, normative legal research is a process to find a legal rule that causes conflict, as in this research, namely in Article 1 Paragraph (1) of the PT Law does not include the term startup or explain the special characteristics of digital startup companies.Findings: The research results show that notaries play a strategic role in the startup legalization process, from verifying the parties' identities and drafting the deed of incorporation to drafting the founder's agreement. The absence of notary intervention at this early stage has the potential to create legal loopholes and corporate disputes. Therefore, strengthening the role of notaries through affirmative policies within the OSS system and increasing notaries' legal capacity in the digital sector is necessary.Implication This research is expected to have an impact on increasing legal certainty in the field of startup establishment in Indonesia, including in relation to strengthening the position and role of notaries.